Storyworlds: helpers - Gaines, Keith (Heinemann UK, 2009)
"Helpers" by Storyworld is a charming storybook that introduces young readers to various community helpers and their important roles. Through engaging illustrations and simple text, it showcases characters such as firefighters, doctors, teachers, and more, highlighting how each helper contributes to the well-being of the community. The book encourages children to appreciate and understand the value of teamwork and service in everyday life.